MORPHOLOGICAL STUDY OF THE SCALES OF Latimeria menadoensis POUYAUD et al - Renny K. Hadiaty; Ike Rachmatika (BRIN Publishing (Penerbit BRIN), 2003)
The scales of Latimeria menadoensis has a variety of the shape of the scales from oval, rectangular, footprint, elongated-pointed edge etc. The comparison in the portion of the exposed and embedded part of the total length of the scales of Latimeria menadoensis and Latimeria chalurnnae at the approximately similar part of the body i.e. scale on the dorsal region and scales located on the region extending lateral posteriorly until caudal, indicated that this portion is different. In L. chalumnae the exposed part are one third and the embedded part are two third of the total length of the scale. The exposed part in the L. menadoensis are more than one third (average 35.9% of total length), while the embedded part are less than tioo third, but 011 the other part of the body i.e. dorsal lobe fin, the embedded part was 73.9% or approximately three [ourth of the total lellgth of tile scale. The 175 loose scales were also examined and discussed. Some of the loose scales ioere examined 1111del' the scanning electron microscope (SEM) by using two kinds of preparations. It showed the apex region, the annular ridges, the radiating ridges and the denticles.